Parkinson's disease and comorbid myasthenia gravis: a case report and literature review - Zhang, Qihao; Xu, Erhe; Li, Hai-Feng; Chan, Piu; Zhao, Zhenzhen; Ma, Jinghong (Frontiers in Neurology, 2024)
Background Parkinson's disease (PD) is the second most common neurodegenerative disease after Alzheimer's disease. Myasthenia gravis (MG) is a rare autoimmune disease caused by antibodies against the neuromuscular junction. PD and comorbid MG are rarely seen. Case presentation Here we report on a patient who was diagnosed with PD and MG. A 74-year-old man had a 4-year history of bradykinesia and was diagnosed with PD. He subsequently developed incomplete palpebral ptosis, apparent dropped head, and shuffling of gait. The results of neostigmine tests were positive. Repetitive nerve stimulation (RNS) showed significant decremental responses at 3 and 5 Hz in the orbicularis oculi. The patient's anti-acetylcholine receptor (anti-AchR) antibody serum level was also elevated. Meanwhile, 9-[18F]fluoropropyl-(+)-dihydrotetrabenazine positron emission tomography–computed tomography (18F-AV133 PET-CT) scan revealed a significant decrease in uptake in the bilateral putamen. After addition of cholinesterase inhibitors, his symptoms of palpebral ptosis and head drop improved greatly and he showed a good response to levodopa. Conclusion Although PD with MG is rare, we still need to notice the possibility that a PD patient may have comorbid MG. The underlying mechanism of PD and comorbid MG remains unknown, but an imbalance between the neurotransmitters dopamine and acetylcholine and the immune system are likely to play significant roles in the pathogenesis. In this article, we present our case and a literature review on the co-occurrence of PD and MG, reviewing their clinical features, and discuss the underlying pathogenic mechanism of this comorbidity.